2007
DOI: 10.1002/tea.20180
|View full text |Cite
|
Sign up to set email alerts
|

Teacher and school characteristics and their influence on curriculum implementation

Abstract: Reform-based curriculum materials have been suggested as a mechanism to make inquirybased instruction more prevalent in secondary science classrooms, specifically when accompanied by comprehensive professional development (Loucks-Horsley, Hewson, Love, & Stiles, 1998;Powell & Anderson, 2002). This research examines the implementation of a reform-based high school chemistry curriculum in a large, urban school district. We explicitly consider the role of the teachers' knowledge and beliefs in their implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
145
0
35

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(185 citation statements)
references
References 39 publications
5
145
0
35
Order By: Relevance
“…En ambos casos se puede llegar a enunciar líneas de actuación que pasan por la superación de un modelo en el que el conocimiento científico adquirido en la licenciatura -creencias del profesorado- (Roehrig, Kruse y Kern, 2007) resulta claramente insuficiente para tomar decisiones sobre qué enseñar y cómo hacerlo (Valcárcel y Sánchez, 2000), pues la ausencia de formación didáctica repercute negativamente en el propio conocimiento del contenido (Mellado y González, 2000) y en la forma de enseñar posterior más que cualquier capacitación didáctica (Porlán, Rivero y Martín, 1998). Los distintos modelos que han surgido en los últimos años consideran especialmente la influencia de este componente.…”
Section: Modelos De Formación Inicial Del Profesoradounclassified
“…En ambos casos se puede llegar a enunciar líneas de actuación que pasan por la superación de un modelo en el que el conocimiento científico adquirido en la licenciatura -creencias del profesorado- (Roehrig, Kruse y Kern, 2007) resulta claramente insuficiente para tomar decisiones sobre qué enseñar y cómo hacerlo (Valcárcel y Sánchez, 2000), pues la ausencia de formación didáctica repercute negativamente en el propio conocimiento del contenido (Mellado y González, 2000) y en la forma de enseñar posterior más que cualquier capacitación didáctica (Porlán, Rivero y Martín, 1998). Los distintos modelos que han surgido en los últimos años consideran especialmente la influencia de este componente.…”
Section: Modelos De Formación Inicial Del Profesoradounclassified
“…In a study by Haney, Lumpe, Czerniak, and Egan (2002), teacher beliefs were found to predict subsequent classroom action for five of the six teachers observed. In general, teachers with more traditional beliefs will implement more traditional or "low-level" technology uses, whereas teachers with more constructivist beliefs will implement more student-centred or "high-level" technology uses (Judson, 2006;Roehrig et al, 2007). Hermans and his colleagues noted "traditional beliefs had a negative impact on integrated use of computers" (p. 1499).…”
Section: Definition Of Teachers' Beliefsmentioning
confidence: 99%
“…The inservice teachers' reasons for not using the new curriculum supported the conclusion of Roehrig, Kruse, and Kern (2007), that even though many science curriculum documents are meant to be inquiry-based, the same does not translate into practice because teachers lack understanding about inquiry and inquiry-based curricula. Therefore, the perceived positive influence of the CAIC on the teachers' abilities echoed critical sentiments by Davis (2002), that curriculum change should be gradual and systematic if it is to truly influence teachers' classroom practice.…”
Section: Modeling and Explorationmentioning
confidence: 97%
“…Recent studies by Roehrig, Kruse, and Kern (2007) revealed that "despite the central role of science as inquiry in science education reform documents, there is little evidence that teaching in K-12 classrooms is, in fact, centered around inquiry (p. 884). At the elementary levels, some studies reported that "even when using inquiry-based science curriculum materials, elementary teachers may not always effectively engage students in science as inquiry" (Forbes & Davis, 2010, p. 820).…”
Section: Inquiry-based Curricula and Teacher Changementioning
confidence: 99%
See 1 more Smart Citation